Modern Treatment Principles for Children with Primary Intestinal Lymphangiectasia: Observational Studies Systematic Review - Regina A. Shukenbaeva; Tatiana V. Turti (Педиатрическая фармакология)
Background. Primary intestinal lymphangiectasia (PIL) is severe and rare disease with poor prognosis. Its management is complex due to the lack of clinical guidelines (both Russian and international). Therefore, consideration of modern principles of this pathology treatment is still crucial, it also can improve the quality and life expectancy in these patients.Objective. The aim of the study is to schematize and unify all relevant data on PIL cases over the past 10 years, to identify modern treatment principles for provision of timely medical car. Methods. Systematic review of publications from 2011 to 2021 in PubMed database was performed. Clinical cases, observational studies, and literature reviews were included.Results. Nutrition therapy in the treatment of PIL has many advantages and it is the firstline therapy. However, modern medicine allows to help children with this pathology via somatostatin group drugs, immunosuppressants, and surgery in case of insufficient nutrition correction.Conclusion. Primary intestinal lymphangiectasia has certain scientific interest in pediatricians and gastroenterologists’ practice. Understanding of the disease, its early diagnosis and pathological process localization allow us to choose the correct diet, to determine the need for surgical intervention, and to prescribe targeted drug therapy.